Psychiatric disorders and obesity: A review of association studies - Rajan, TM; Menon, V (Journal of postgraduate medicine, 2017)
Inconsistent evidence exists regarding the strength, direction, and moderators in the relationship between obesity and psychiatric disorders. This study aims to summarize the evidence on the association between psychiatric illness and obesity with particular attention to the strength and direction of association and also the possible moderators in each postulated link. Systematic electronic searches of MEDLINE through PubMed, ScienceDirect, PsycINFO, and Google Scholar were carried out from inception till October 2016. Generated abstracts were screened for eligibility to be included in the review. Study designs that evaluated the strength of relationship between obesity and psychiatric disorders were included in the study. Quality assessment of included studies was done using the Newcastle-Ottawa checklist tool. From a total of 2424 search results, 21 eligible articles were identified and reviewed. These included studies on obesity and depression (n = 15), obesity and anxiety (four) and one each on obesity and personality disorders, eating disorder (ED), attention deficit hyperactivity disorder, and alcohol use. Maximal evidence existed for the association between depression and obesity with longitudinal studies demonstrating a bidirectional link between the two conditions. The odds ratios (ORs) were similar for developing depression in obesity (OR: 1.21-5.8) and vice versa (OR: 1.18-3.76) with a stronger association observed in women. For anxiety disorders, evidence was mostly cross-sectional, and associations were of modest magnitude (OR: 1.27-1.40). Among other disorders, obesity, and EDs appear to have a close link (OR: 4.5). Alcohol use appears to be a risk factor for obesity and not vice versa but only among women (OR: 3.84). Obesity and depression have a significant and bidirectional association. Evidence is modest for anxiety disorders and inadequate for other psychiatric conditions. Gender appears to be an important mediator in these relationships.